2018
DOI: 10.18632/oncotarget.24569
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consequences of HIF silencing in a triple negative human breast cancer xenograft

Abstract: Hypoxia is frequently encountered in tumors and results in the stabilization of hypoxia inducible factors (HIFs). These factors transcriptionally activate genes that allow cells to adapt to hypoxia. In cancers, hypoxia and HIFs have been associated with increased invasion, metastasis, and resistance to chemo and radiation therapy. Here we have characterized the metabolic consequences of silencing HIF-1α and HIF-2α singly or combined in MDA-MB-231 triple negative human breast cancer xenografts, using non-invasi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 44 publications
0
19
0
1
Order By: Relevance
“…Nevertheless, hypoxic cells are thought to preferably derive FAs from increased uptake by upregulating FA binding proteins (FABPs), needed for FA uptake and intracellular trafficking, and predominantly utilize de novo lipid and FA synthesis from acetyl-CoA in nutrient-deprived conditions (77). Acetyl-CoA can be supplied through import of acetate, which is directly converted to acetyl-CoA in the cytoplasm by the HIF target ACSS2 (6,71,77,79).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…Nevertheless, hypoxic cells are thought to preferably derive FAs from increased uptake by upregulating FA binding proteins (FABPs), needed for FA uptake and intracellular trafficking, and predominantly utilize de novo lipid and FA synthesis from acetyl-CoA in nutrient-deprived conditions (77). Acetyl-CoA can be supplied through import of acetate, which is directly converted to acetyl-CoA in the cytoplasm by the HIF target ACSS2 (6,71,77,79).…”
Section: Lipid Metabolismmentioning
confidence: 99%
“…A recent study showed that HIF1 is associated with choline metabolism in breast and prostate cancer, and that it activates CHKα by activating hypoxia response elements, thereby increasing cellular PC and choline levels . The silencing of HIF1α and HIF2α were shown to reduce cellular GPC levels in breast cancer cells . It is currently not known how other transcription factors such as AP‐1, GATA‐3, FOXA1, Snail1/2, Twist1/2, ZEB1/2, and NFAT, STAT‐3/−5 and Notch affect choline metabolism in cancer, and GPC levels in particular.…”
Section: Oncogenic Signaling Pathways and Transcription Factors Regulmentioning
confidence: 99%
“…The picture is further complicated because ChoK is not the only enzyme that contributes to PC accumulation; it can be produced directly by the actions of PLC on PtdCho, or by the hydrolysis of GPC as a source of additional choline for subsequent phosphorylation. Recent MRS applications have been used to detect changes in choline metabolism due to IDH mutations in glioma, explore the role of the glycerophosphodiesterase genes GDPD5 and GDPD6 on breast cancer cell migration/invasion, and profile metabolic changes in response to HIF1 and HIF2 suppression …”
Section: Imaging Metabolic Lipid Changesmentioning
confidence: 99%